APPRECIATION FROM THE POINT OF VIEW OF THE CERTIFIED PUBLIC ACCOUNTANT. - Wildman, John R. (The Accounting Review, 1928)
Abstract The certified public accountant's interest in the subject of appreciation is a practical one. He is forced to consider the matter in connection with his review of accounting and his certification of financial statements. The facts are, whether or not such procedure is justifiable, that physical property and intangible frequently are revalued by, or at the instance of, the owners of such possessions who attempt, in various ways, to give expression to the estimated increases in value. The certified public accountant, therefore, is confronted primarily with a condition; not a theory. The authority for the restated value may be either a report of independent appraisers, or a resolution of corporation directors. In as much as the certified public accountant does not attempt to act as an appraiser, to pass judgment on the work of such persons, or to assume responsibility for the values which they fix, he accepts their judgment and qualifies his statements accordingly. The occasions for revaluations which give rise to estimated increases in values are various.